2022
DOI: 10.3389/fneur.2022.906317
|View full text |Cite
|
Sign up to set email alerts
|

Global Trend in the Research and Development of Acupuncture Treatment on Parkinson's Disease From 2000 to 2021: A Bibliometric Analysis

Abstract: BackgroundAcupuncture has been widely used in the treatment of patients with Parkinson's disease (PD) in the world. Despite we have an in-depth understanding of acupuncture in this field over the past years, there is no available literature on bibliometric analysis on the development of acupuncture on PD. This study was designed to explore the global trend in the research of acupuncture on PD in the recent 20 years by the software CiteSpace (5.8.R3) and VOSviewer (1.6.14).MethodsPublications regarding acupunct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 49 publications
0
11
0
Order By: Relevance
“…In terms of mechanistic studies, the absence of dopaminergic neurons in the nigrostriatal pathway is the most common pathological factor in PD. Acupuncture can mitigate brain dopaminergic neuronal damage through various pathways, such as apoptotic pathway, autophagic pathway, oxidative stress-related pathway, survival pathway, and neurotransmitter and its receptor and neurotrophic factor expression, thereby achieving neuroprotective mechanisms ( 15 , 28 , 29 ). In recent years, the gut–brain axis has offered a potential entry point for the treatment of PD as the gut–brain axis theory proposes a close connection between the gastrointestinal tract and the central nervous system ( 47 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In terms of mechanistic studies, the absence of dopaminergic neurons in the nigrostriatal pathway is the most common pathological factor in PD. Acupuncture can mitigate brain dopaminergic neuronal damage through various pathways, such as apoptotic pathway, autophagic pathway, oxidative stress-related pathway, survival pathway, and neurotransmitter and its receptor and neurotrophic factor expression, thereby achieving neuroprotective mechanisms ( 15 , 28 , 29 ). In recent years, the gut–brain axis has offered a potential entry point for the treatment of PD as the gut–brain axis theory proposes a close connection between the gastrointestinal tract and the central nervous system ( 47 ).…”
Section: Discussionmentioning
confidence: 99%
“…Although existing systematic evaluations and meta-analyses have shown conflicting results for acupuncture for PD constipation due to significant heterogeneity and small sample sizes (20)(21)(22)(23)(24), the fact that acupuncture was considered an effective or safe treatment for functional constipation and gastrointestinal disorders (25,26) in some randomized trials. Available evidence suggests that acupuncture treatment has the potential to alleviate motor and NMS of PD, but the underlying mechanisms are unclear (27)(28)(29). The neuroprotective effects of acupuncture on neurodegenerative lesions in animal models of PD are mainly focused on cerebral neurons (30)(31)(32), and no studies have yet reported the effects of acupuncture on the ENS.…”
Section: Introductionmentioning
confidence: 99%
“…Keyword analysis helps identify research hotspots and predicts developing trends in the field ( 57 ). As indicated in Figures 8B , 9 , the following keywords may indicate the recent focus and research hotspots: “trauma management,” “neurocritical care,” “injury severity,” and “emergency medical service.”…”
Section: Discussionmentioning
confidence: 99%
“…Similar to natural medicines, acupuncture has fewer side effects and is therefore more suitable for longterm treatment of PD than synthetic drugs [67]. Acupuncture is currently used as a complementary and alternative therapy for PD in many countries [68][69][70][71]. Studies have shown that acupuncture significantly improves motor symptoms and NMSs in PD [37][38][39][72][73][74].…”
Section: Discussionmentioning
confidence: 99%